THE ROLE OF NONVERBAL COMMUNICATION IN IMPROVING INTERPERSONAL RELATIONSHIPS IN THE WORKPLACE - Nadia, Rafa; Syam, Abdi Mubarak (Pena Cendekia Insani, 2025)
Nonverbal communication plays a strategic role in fostering effective interpersonal relationships, particularly in dynamic work environments such as the event organizer (EO) industry. This study is motivated by the limited research that specifically explores how nonverbal communication elements enhance coordination and team interaction quality in high-pressure EO settings. The primary aim of this research is to analyze the role of nonverbal communication in strengthening interpersonal relationships within the EO workplace and to identify the most influential nonverbal cues contributing to team effectiveness. This research employs a qualitative approach using a case study method at a selected EO company in Medan, Indonesia. Data were collected through in-depth interviews, participant observation, and documentation. The study involved purposively selected participants, including supervisors, event coordinators, field staff, and liaison officers, based on their direct experience with team communication. The findings reveal that nonverbal elements such as facial expressions, eye contact, hand gestures, and body posture play crucial roles in conveying instructions, fostering team unity, and building trust among team members and with clients. However, challenges such as cultural differences in interpreting nonverbal cues and high work pressure sometimes hinder effective communication. The study concludes that nonverbal communication serves as a vital tool in creating cohesive teamwork and a harmonious working atmosphere in EO environments. Practically, this research implies the need for structured nonverbal communication training for EO staff to improve coordination and minimize misunderstandings. Academically, it contributes to the development of organizational communication studies and offers a foundation for future research in creative industries and other high-pressure work settings.